IMPLEMENTASI PROGRAM REHABILITASI MEDIS PENGGUNA NARKOTIKA PADA BADAN NARKOTIKA NASIONAL (BNN) KABUPATEN SUMEDANG (JRPA - Journal of Regional Public Administration, 2023)
This article is the result of research on the implementation of the medical rehabilitation program at the Sumedang District Office of the National Narcotics Agency (BNNK), including the obstacles in implementation, and efforts to overcome these obstacles. The implementation of this program is analyzed through four logical model elements from McDavid et al., namely: inputs, components, implementation activities, and outputs. A qualitative approach is the method used in this study with data sources obtained through interviews, literature studies and field studies. The findings from the study were that the implementation of the medical rehabilitation program at the Sumedang BNNK office had been carried out in accordance with the provisions stipulated in a structured implementation flow through the establishment of an Integrated Assessment Team made by the Sumedang BNNK. However, in practice this program experienced several obstacles so that its implementation was seen as not optimal, including the unavailability of separate counseling rooms from other rooms, the difficulty of adjusting the time between officers and clients in the process of medical rehabilitation activities, and the inadequate quality of staff resources, especially those who support activities medical rehabilitation. In overcoming these obstacles several efforts have been made, including submitting a proposal to create a separate counseling room that can maintain the privacy of the client, increasing communication between officers with both the client and the client's family in determining and adjusting the time, as well as providing training or competency exams for officers. who are not certified.